Type of muscle fibre and its relationship to the Speech-Language Pathology approach in swallowing disorders - González, Gabriel (Revista Chilena de Fonoaudiología, 2020)
Swallowing intervention protocols in dysphagia do not specify the parameters of the exercises, namely the duration, frequency and number of series, all of which present a challenge in speech therapy intervention in swallowing disorders. The purpose of this review is to provide Speech and Language Pathologists with background information concerning crucial muscle fibres used in swallowing therapy and to subsequently indicate appropriate skull-cervical-oral muscle exercises. We describe the primary muscle and its characteristics such as fatigue resistance and contraction speed, review the types of fibres of some of the main muscles that participate in the swallowing process, and present the particularities of the muscles of the cranio-cervical-oral area in comparison with the rest of the skeletal muscles. We also provide information regarding the difficulties in evaluating the musculature involved in the swallowing process before finally highlighting the relevance of understanding the roles and characteristics of these muscles for clinical practice.